Mişcarea naturală a populaţiei. România în contextul statelor membre ale Uniunii Europene. - Mărginean, Ioan (Calitatea Vieții, 2016)
This paper contains an analysis on vital statistics in Romania, for post war period. There are taken into consideration several indices like: birth, fertility, mortality, natural change rates and life expectancy also. The source of the data is, in principle, Statistical Yearbook (National Institute of Statistics). Through these analyses, we can even see some variations of the indicator’s values it put into evidence, on one part, a descendent trend for birth, fertility and natural change rates and, on other part, an increasing in general mortality rate. The result is the negative natural change rate in Romania, starting with the year 1992. In the same time, it is to notice the increase of life expectancy and the reduction of infant mortality. Even so, between European Union Member States, Romania has some of the most unfavourable position. Considering this situation, it is necessary to adopt public policy measure to improve quality of life of the population. This means firstly to adopt important actions to improve health care, education systems and others social services.